Pengaruh Utang Luar Negeri dan Ekspor Terhadap Pertumbuhan Ekonomi (PDB) Indonesia Periode Tahun 2006-2020 - Anis Farida; Indah Yuliana (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
This review is expected to be able to carry out a test with the ultimate goal of deciding on the variables that affect Indonesia's GDP. This type of review uses a quantitative methodology. The factors in this review are the value of Indonesia's external debt and the value of Indonesia's GDP as the dependent factor and the value of Indonesia's GDP as the dependent factor. This information is taken as selected information (time series) from BI and the Central Statistics Agency for the period 2006-2020. This information checking technique uses multiple linear regression examination. The impact of this review proves that the relationship between Indonesia's external debt and the value of Indonesian exports has a very large impact together. The fractional test (t test) proves that the value of Indonesia's external debt basically has an impact on the value of Indonesia's economic growth. The export value factor does not affect the value of gross domestic product in Indonesia.